Skin temperatures of a pre-cooled wet person exposed to engulfing flames. (April 2017) - Log, Torgrim
Abstract: In a television show, a wetted bare-skinned person slid through engulfing kerosene pool fire flames. The 0.74 s flame exposure resulted in pain and light sun burns. The heat and mass transfer involved in this dangerous stunt have been analyzed in order to evaluate whether or not the thin water layer represented an important heat protection measure. It is estimated that the wetted person was exposed to heat fluxes in the range of 80–90 kW/m 2 . Analytical solutions of the heat equation were used to evaluate water-spray pre-cooling, heating during flame exposure and post-flame relaxation of skin temperature gradients. It is shown that the water layer carried on the skin into the flames represented limited heat protection. The 30 s cold water-spray pre-cooling prior to the flame exposure was the most important heat protection mechanism. Larger flames of higher emissivity, longer period of flame exposure, warmer pre-cooling water or shorter pre-cooling period would most likely have resulted in severe skin burns.